SYSTEMATIC ANALYSIS OF THE POTENTIAL USE OF GAMIFICATION ELEMENTS IN THE TRAINING OF FUTURE COMPUTER SCIENCE TEACHERS - Aldabergenova А.; Yesseikyzy У.; Yessengabylov И.; Yesseikyzy А. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2025)
This study presents a systematic review of the application of gamification in higher education between 2020 and 2025. The methodological foundation is based on the PRISMA protocol, which ensured a multi-stage search, screening, and structured selection of publications. An analysis of Web of Science, Scopus, Google Scholar, and ResearchGate databases identified 3451 publications, of which 42 full-text studies were included in the final sample after removing duplicates and applying inclusion criteria. The data analysis employed thematic classification, content analysis, and visualization using Microsoft Excel, VOSviewer, and Datawrapper. The findings indicate that the most frequently used gamification elements in university teaching include points, badges, levels, and leaderboards, which demonstrate consistently positive effects on students’ motivation, engagement, and academic activity. Less common mechanics related to progress, rewards, and competition are used selectively and show more variable outcomes. Special attention in this study is given to the potential use of gamification in the training of future computer science teachers. The identified elements possess various pedagogical benefits, including the development of motivation, autonomy, active learning behaviors, and problem-solving skills, making them particularly relevant for the methodological preparation of future educators. The practical significance of the study lies in the fact that its results can be used in the development of gamified instructional materials and digital courses in computer science teaching methodology.